Comparative analysis of cerebrospinal fluid biomarkers in the differential diagnosis of neurodegenerative dementia. Issue 5 (21st December 2015) - Llorens, Franc; Schmitz, Matthias; Karch, André; Cramm, Maria; Lange, Peter; Gherib, Kerim; Varges, Daniela; Schmidt, Christian; Zerr, Inga; Stoeck, Katharina
Abstract: Introduction: The analysis of cerebrospinal fluid biomarkers gains importance in clinical routine and is effective in substantiating dementia diagnosis in the differential diagnostic context. Methods: We evaluated the levels of β‐amyloid (Aβ) 42, Aβ40, tau, and P‐tau in a large patient population subdivided into prion diseases, tauopathies, synucleinopathies, and controls. Diagnostic test evaluation was assessed by ROC area under the curve analysis. Results: High tau levels were detected in sporadic Creutzfeldt‐Jakob disease (sCJD) and high P‐tau levels in Alzheimer's disease (AD) and sCJD. Aβ40 was lower exclusively in prionopathies, but low Aβ42 was detected in AD, sCJD, and Lewy body dementia. When disease groups were stratified according to the underlying proteinopathy, we detected disease‐type specificities for all biomarkers. P‐tau/tau, Aβ42/40, Aβ42/tau, and Aβ40/tau ratios proved valuable in discriminating disease groups and controls, especially P‐tau/tau ratio in the identification of sCJD cases. Discussion: Combining the biomarker panel allows differentiating between various types of neurodegenerative dementias and contributes to a better understanding of their pathophysiological processes.